COVID-19 Monitoring Survey in Poor and Slum Areas of Dhaka and Chittagong : Bangladesh Labor Market Situation As of Round 3, January 13 - February 27, 2021 - World Bank (World Bank, Washington, DC, 2021)
To track the impacts of the COVID-19 crisis on labor markets and household coping strategies, a rapid phone survey was implemented on a representative sample of households living in poor and slum areas of Dhaka and Chittagong City Corporations (CCs). This brief, the fifth in the series, summarizes results from the first, second, and third rounds of the rapid phone survey, conducted from June 10 to July 10, 2020, from September 2 to October 11, 2020, and from January 13 to February 27, 2021, respectively. Eighty-eight percent of respondents interviewed in the first and second survey rounds were reached in the third round (see annex 1 for details of the survey design and response rates). This brief focuses on how the labor-market situation evolved between the rounds a year after the onset of the crisis.